Landing on a small tropical island: Wide in-situ diversification of an urban-dwelling bat - Samantha Aguillon; Clara Castex; Avril Duchet; Magali Turpin; Gildas Le Minter; Camille Lebarbenchon; Axel O.G. Hoarau; Céline Toty; Léa Joffrin; Pablo Tortosa; Patrick Mavingui; Steven M. Goodman; et al. (Global Ecology and Conservation, 2024)
Island endemic bats are a considerable cause of conservation concerns, as islands are vulnerable ecosystems facing natural and anthropogenic threats such as growing urbanization. Here, we studied the Reunion free-tailed bat (Mormopterus francoismoutoui), an endemic species to Reunion Island that has adapted to urban settings. We investigated the evolutionary history of Mormopterus at a regional scale, as well as on Reunion Island sex-specific and seasonal patterns of genetic structure. We used an extensive spatio-temporal sampling including 1136 individuals from 18 roosts and three biological seasons (non-reproductive/winter, pregnancy/summer, and mating), with additional samples of Mormopterus species from neighbouring islands (M. jugularis from Madagascar and M. acetabulosus from Mauritius). Complementary information gathered from both microsatellite and mitochondrial markers revealed high genetic diversity but no signal of spatial genetic structure and weak evidence of female philopatry. Regional analysis suggests a single colonization event for M. francoismoutoui, dated around 175,000 years ago, and followed by in-situ diversification and the evolution of divergent ancestral lineages, which today form a large metapopulation. Population expansion was relatively ancient (55,000 years ago) and thus not linked to human colonization and the availability of human-constructed day-roost sites. Discordant structure between mitochondrial and microsatellite markers suggests the presence of yet-unknown mating sites, or the recent evolution of putative ecological adaptations. Our study illustrates the challenge of detailed genetic studies to provide critical insights to insular ecology and evolutionary history, and the importance of both mitochondrial and nuclear DNA in exploring in-situ diversification of an urban-dwelling bat, endemic to a small island.